Subjective health of adolescents from families in receipt of social assistance. (August 2016) - Mazur, J.; Dzielska, A.; Zawadzka, D.; Tabak, I.; Małkowska-Szkutnik, A.
Abstract: Objective: To compare the subjective health of adolescents from families in receipt and not in receipt of social assistance. Study design: Nationwide cross-sectional study of 1812 pupils aged 13–18 years in Poland in 2010–2011. Methods: The analysis focused on two dimensions of the Child Health and Illness Profile – Adolescent Edition questionnaire: discomfort and satisfaction with health. Age, sex and seven socio-economic factors were considered as determinants. Results: Overall, 10.8% of the respondents reported that their families were in receipt of social welfare benefits. Among the families of low socio-economic status and living in poor regions, the percentage in receipt of social welfare benefits increased to 22.1%; however, this figure was lower (4.4%) if both parents had a higher level of education. After adjustment for six sociodemographic variables, the standardized regression coefficient of the social welfare benefits variable amounted to 0.072 ( P = 0.004) in the discomfort model and −0.044 ( P = 0.079) in the satisfaction model. A significant three-level interaction was found ( P = 0.007) between residential location, neighbourhood affluence and being in receipt of social welfare benefits as predicators of discomfort score (general linear model). Conclusions: Being in receipt of social welfare benefits has a stronger impact on experiencing discomfort than diminishing satisfaction with one's health. It also has a stronger effect on physical problems than on emotional problems. The item 'on social assistance' is recommended as it helps to identify families particularly exposed to the health consequences of poverty. Highlights: Social assistance granted to the family can be regarded in health surveys as an indicator of family deprivation. Adolescents from families receiving social assistance reported worse health, even when adjusted for other factors. A stronger impact of receiving social assistance on physical than on emotional problems has been found. Information on social assistance provided by adolescents seems to be reliable but validation studies are needed.